2015
DOI: 10.1128/aac.01816-15
|View full text |Cite
|
Sign up to set email alerts
|

Griffithsin and Carrageenan Combination To Target Herpes Simplex Virus 2 and Human Papillomavirus

Abstract: Extensive preclinical evaluation of griffithsin (GRFT) has identified this lectin to be a promising broad-spectrum microbicide. We set out to explore the antiviral properties of a GRFT and carrageenan (CG) combination product against herpes simplex virus 2 (HSV-2) and human papillomavirus (HPV) as well as determine the mechanism of action (MOA) of GRFT against both viruses. We performed the experiments in different cell lines, using time-of-addition and temperature dependence experiments to differentiate inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
111
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 44 publications
(62 reference statements)
3
111
0
Order By: Relevance
“…In in vitro studies, GRFT showed weak-to-moderate activity in blocking HSV-2 entry, yet it was capable of inhibiting cell-to-cell spread with IC 50 s in the nanomolar range [34,42]. In in vivo studies using a murine model, a gel containing 0.1% GRFT significantly protected mice from HSV-2 challenge compared to the control group.…”
Section: Antiviral Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…In in vitro studies, GRFT showed weak-to-moderate activity in blocking HSV-2 entry, yet it was capable of inhibiting cell-to-cell spread with IC 50 s in the nanomolar range [34,42]. In in vivo studies using a murine model, a gel containing 0.1% GRFT significantly protected mice from HSV-2 challenge compared to the control group.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Though GRFT treatment led to a small decline in epithelial barrier integrity in polarized cell cultures, no increase in HIV migration was observed establishing its safety for HSV-2 prevention [42]. In vitro binding and immunoprecipitation studies suggest GRFT blocks HSV-2 infection by interacting with one of the four glycoproteins involved in HSV-2 entry, namely glycoprotein D [34]. …”
Section: Antiviral Activitymentioning
confidence: 99%
See 3 more Smart Citations